Tlingit gravestone, Wrangell, Alaska, May 26, 1908. - Cobb, John N.
Carved marble gravestone, Wrangell, Alaska Note from Cobb field notebook: Indian grave at Wrangell, Alaska. Note from unidentified source: With carved marble headstone.